An investigation of relationship between global economic sanction and life expectancy: do financial and institutional system matter?. Issue 1 (31st December 2022) - Ha, Le Thanh; Nam, Pham Xuan
ABSTRACT: This article examines the impact of cross-border economic sanctions (CES) on the quality of national health – proxied by life expectancy. Structural gravity models are employed for a sample of 148 sanctioned countries (108 developing countries and 40 developed countries) during the 1995–2018 period. We consider various forms of sanction, including arms, military, trade, finance and travel. The results reveal that the imposition of sanctions, especially arm, financial, travel and other sanctions, has a significant negative effect on the national health of the targeted countries. The effects are largely heterogeneous across sanctioned countries in terms of their economic development. Furthermore, financial market development and institutional quality of the sanctioned countries critically affect the relationship between CES and national health. Particularly, more developed financial markets, the higher degree of financial openness and central bank independence, as well as higher institutional quality, help targeted countries alleviate the consequences of CES on national health. These empirical findings are expected to provide insightful lessons for economists and policymakers in the targeted countries facing the risk of economic degradation.